Determinants of tax non-compliance among small and medium-sized corporations in Sarawak: tax audit data - Clement Jackoi, Bernard Empam (2020)
One of country's sources of income to stimulus economic development is based on a tax managed to be collected. In Malaysia, the Inland Revenue Board of Malaysia (TRBM) is an agency appointed to govern the direct tax collection which is known as income tax. Income tax is the main contributor to most of the country's revenue. Performance statistics shown that the tax collection reported by the IRBM increasing annually. However, non-compliance issue tremendously increased with an increase in the number of tax audit cases finalized with audit adjustments and penalties. This study is carried out to identify the determinant of non-compliance among the Small and Medium Corporations (SMCs). Secondary data is obtained from the IRBM taxation Audit Case Management System as quantitative data for the purpose of this study. Samples of the study population used the SMCs tax audit case finalized in year 2018 at Sarawak's IRBM branches. The focus of the study is on company location, industry type, company size and financial liquidity of SM Cs. The results showed that there was a significant difference between SMCs tax non-compliance in Sarawak branches and the type of industry as well as the size of the company factors. However, there is no significant difference between SM Cs tax non-compliance in Sarawak branches and the company location and company's financial liquidity factors. The result of this study is expected to provide additional information to tax literatures and assistance to the IRBM in Sarawak to enhance the tax compliance among SMCs in Sarawak.